Sensitive monitoring of monoterpene metabolites in human urine using two-step derivatisation and positive chemical ionisation-tandem mass spectrometry. - Schmidt, Lukas; Belov, Vladimir N.; Göen, Thomas (Analytica chimica acta, 2013)
A gas chromatographic-positive chemical ionisation-tandem mass spectrometric (GC-PCI-MS/MS) method for the simultaneous determination of 10 oxidative metabolites of the monoterpenoid hydrocarbons α-pinene, (R)-limonene, and Δ(3)-carene ((+)-3-carene) in human urine was developed and tested for the monoterpene biomonitoring of the general population (n=36). The method involves enzymatic cleavage of the glucuronides followed by solid-supported liquid-liquid extraction and derivatisation using a two-step reaction with N,O-bis(trimethylsilyl)-trifluoroacetamide and N-(trimethylsilyl)imidazole. The method proved to be both sensitive and reliable with detection limits ranging from 0.1 to 0.3 μg L(-1). In contrast to the frequent and distinct quantities of (1S,2S,4R)-limonene-1,2-diol, the (1R,2R,4R)-stereoisomer could not be detected. The expected metabolite of (+)-3-carene, 3-caren-10-ol was not detected in any of the samples. All other metabolites were detected in almost all urine samples. The procedure enables for the first time the analysis of trace levels of a broad spectrum of mono- and bicyclic monoterpenoid metabolites (alcohols, diols, and carboxylic acids) in human urine. This analytical procedure is a powerful tool for population studies as well as for the discovery of human metabolism and toxicokinetics of monoterpenes.